2011
DOI: 10.1177/0956797611419519
|View full text |Cite
|
Sign up to set email alerts
|

Status, Race, and Money

Abstract: A deeply entrenched status hierarchy in the United States classifies African Americans as lower status than Caucasians. Concurrently, African Americans face marketplace discrimination; they are treated as inferior and poor. Because having money and spending money signify status, we explored whether African Americans might elevate their willingness to pay for products in order to fulfill status needs. In Studies 1 and 2, explicit activation of the race concept led some African Americans to pay more than they wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…It is well established that the symbols used by different social-demographic groups to demonstrate status differ within clusters of countries sharing similar cultural attributes (Hofstede et al 2010). It is also well documented that these symbols are dynamic and ever changing (Bourdieu, 1984;Ivanic et al, 2011;Linssen et al, 2011;Bloch et al, 2004). Leaving practical constraints and factors aside, there are several potential explanations for this.…”
Section: Symbolic Transport Motivation Across Different Groups and Cumentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the symbols used by different social-demographic groups to demonstrate status differ within clusters of countries sharing similar cultural attributes (Hofstede et al 2010). It is also well documented that these symbols are dynamic and ever changing (Bourdieu, 1984;Ivanic et al, 2011;Linssen et al, 2011;Bloch et al, 2004). Leaving practical constraints and factors aside, there are several potential explanations for this.…”
Section: Symbolic Transport Motivation Across Different Groups and Cumentioning
confidence: 99%
“…Migrant status could also be influential: Sheel (2005) examined the purchasing habits of the Indian migrant community living in Canada and observed that there is often extreme family pressure on younger people to drive a 'good car' to show relatives back in India that they have been successful in the 'new country' (see also Ivanic et al, 2011;Kaus, 2013). Finally, gender, and mate attraction, could also be motivating factors -Dunn and Searle (2010) describe how males are generally rated as more attractive by females when driving a luxury car than a small old vehicle, regardless of the social status of the female participants in the survey; they also note how many car adverts use mate attraction as a motivator.…”
Section: Symbolic Transport Motivation Across Different Groups and Cumentioning
confidence: 99%
“…Migrant status could also be influential: Sheel (2005) examined the purchasing habits of the Indian migrant community living in Canada and observed that there is often extreme family pressure on younger people to drive a 'good car' to show relatives back in India that they have been successful in the 'new country' (see also Ivanic et al, 2011;Kaus, 2013). Finally, gender, and mate attraction,…”
Section: Symbolic Transport Motivation Across Different Groups and Cumentioning
confidence: 99%
“…Empirical work on racial differences in consumption, however, has focused on narrow categories of goods and service and proposed individual-level explanations only. Drawing on the Veblenian concept of conspicuous consumption (Veblen 1899), scholars have argued that black consumers devote a greater portion of their resources to visible, status-increasing goods (Charles, Hurst and Roussanov 2009; Ivanic, Overbeck and Nunes 2011). This conspicuous consumption is variously presented as a rational strategy for managing racially motivated microaggressions (Lamont and Molnar 2001; Lee 2000) or as a problematic form of spending leading to lower investments in productive assets (Moav and Neeman 2010; Rayo and Becker 2006).…”
Section: Approaches To Race and Consumptionmentioning
confidence: 99%